Мультимедійні видання для дітей - Ісаєнко, Т. Ю. (ХНУРЕ, 2021)
The main difference between printed and multimedia publications is the possibility of interactive implementation, in which the user (reader) can not only navigate through the built-in hyperlinks, but also actively interfere in the course of events, watch animation, view and listen to video and audio. A multimedia publication attracts children more than a printed one, thanks to interactive elements – it turns reading into a video game. In many cases, partial or complete transition to electronic textbooks and computer education technologies is justified.
Keywords: видання; дитяча книга